ASEAN law in the new regional economic order: Global trends and shifting paradigms - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2019)
The fast-growing last decade of strong economic growth of the Association of Southeast Asian Nations (ASEAN) has played a critical role in Asia-Pacific regionalism and global trade. This book explores the concept of ASEAN law under the normative framework of the new regional economic order. It examines the roadmap of the new ASEAN Economic Community Blueprint 2025 by evaluating the impact of ASEAN trade agreements on domestic legislation on professional services, financial integration, investment disputes and digital trade. More importantly, it sheds light on the legal implications of ASEAN's agreements with China and India and the potential developments of mega-regional trade agreements such as the CPTPP and the RCEP. Hence, the legal analysis and case studies in the book offer a fresh view of Asia-Pacific integration and bridge the gap between academia and practice.